War exposure, attachment style, and moral reasoning - Haskuka, Mytaher; Sunar, Diane; Alp, I. Ercan (Sage Publications Inc, 2008)
This study extends the investigation of the effects of war exposure beyond those previously documented (e. g., increased stress and aggression and various types of psychopathology) to include moral reasoning. Three groups from two cultures with different levels of exposure to the 1998-1999 war in Kosovo were compared using Rest's Defining Issues Test. Possible effects of attachment style alone and in interaction with war exposure were also investigated. The results showed that exposure to war has (a) a very strong negative effect on moral reasoning with (b) no moderation by attachment style. However, the evidence suggests that war exposure may change the individual's attachment style from secure to insecure by inducing a more negative model of the other.
Keywords: War Exposure; Moral Reasoning; Attachment Style; İndividualism; Collectivism; Posttraumatic Growth; Early Adulthood; Hong-Kong; Infancy; Discontinuity; Adolescents; Continuity; Interview; Judgment